Efflux Pump Overexpression Contributes to Tigecycline Heteroresistance in Salmonella enterica serovar Typhimurium - Chen, Yi; Hu, Daxing; Zhang, Qijing; Liao, Xiao-Ping; Liu, Ya-Hong; Sun, Jian (Frontiers in Cellular and Infection Microbiology, 2017)
Bacterial heteroresistance has been identified in several combinations of bacteria and antibiotics, and it complicated the therapeutic strategies. Tigecycline is being used as one of the optimal options for the treatment of infections caused by multidrug-resistant Salmonella. This study investigated whether heterorresistance to tigecycline exists in a Salmonella enterica serovar Typhimurium strain harboring the oqxAB-bearing IncHI2 plasmid pHXY0908. MIC and population analyses were performed to evaluate population-wide susceptibility to tigecycline. The effects of efflux pumps on MIC levels were assessed using the efflux pump inhibitor Phe-Arg-β-naphthylamide, measuring intracellular tigecycline accumulation as well as mRNA levels of regulatory and efflux pump genes. DNA sequencing of regulatory regions were performed and plasmid curing from a resistant strain provided an appropriate control. Results showed that MICs of a parental strain with and without pHXY0908 as well as a plasmid-cured strain 14028/Δp52 were 0.5, 1 and 1μg/mL, respectively. Population analysis profiling illustrated that only the pHXY0908-containg strain was heteroresistant to tigecycline. A fraction of colonies exhibited stable profiles with 4 to 8-fold increases in MIC. The frequencies of emergence of these isolates were higher in the plasmid-containing strain pHXY0908 than either the parental or the 14028/Δp52 strain. Phe-Arg-β-naphthylamide addition restored tigecycline susceptibility of these isolates and intracellular tigecycline accumulation was reduced. Heteroresistant isolates of the strain containing pHXY0908 also had elevated expression of acrB, ramA and oqxB. DNA sequencing identified numerous mutations in RamR that have been shown to lead to ramA overexpression. In conclusions, heteroresistance to tigecycline in Salmonella enterica serovar Typhimurium was manifested in a plasmid-bearing strain. Our results suggest that this phenotype was associated with overexpression of the AcrAB-TolC and OqxAB efflux pumps.